2020
DOI: 10.1002/acp.3756
|View full text |Cite
|
Sign up to set email alerts
|

Visual search for drowning swimmers: Investigating the impact of lifeguarding experience

Abstract: How does domain expertise influence dynamic visual search? Previous studies of visual search often use abstract search arrays that are devoid of applied context, with comparatively few studies exploring applied naturalistic and dynamic settings. The current research adds to this literature by examining lifeguard drowning-detection across two studies using naturalistic, dynamic search tasks. Behavioural responses and eye-movement data were recorded as participants watched staged video clips and attempted to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…In summary, Experiment 1 verified that the lifeguard experience effect previously shown by Laxton and Crundall (2018) and Laxton et al (2020) using artificial stimuli is evident when using real drowning scenes. However, it provides little information on the processes underlying this effect.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…In summary, Experiment 1 verified that the lifeguard experience effect previously shown by Laxton and Crundall (2018) and Laxton et al (2020) using artificial stimuli is evident when using real drowning scenes. However, it provides little information on the processes underlying this effect.…”
Section: Discussionsupporting
confidence: 68%
“…Of the few studies that have actually investigated lifeguard visual search, the results support the effect of domain experience in target detection when lifeguards' performance is compared to that of control participants (Laxton & Crundall, 2018;Laxton et al, 2020;Page et al, 2011). However, in the Laxton et al (2020) study it was found that there were no differences in eye-movements between experienced lifeguards and nonlifeguards (e.g., time to first fixate the target, processing time on target, etc.…”
Section: Assessing Lifeguards' Visual Search Skillsmentioning
confidence: 70%
See 3 more Smart Citations